Optimization of culture conditions of immobilized cells for enzyme excretion and cell lysis - Rohaida, Che Man; Rosli, Md Illias; Aizi Nor Mazila, Ramli; Siti Kholijah, Abdul Mudalip (Wiley, 2022)
Recombinant enzyme excretion is essential due to stable and active protein production. However, enzyme excretion, especially in the Escherichia coli system, may increase the occurrence of cell lysis. Thus, cell immobilization was used, and optimization of culture conditions was conducted to increase enzyme excretion and limit cell lysis. The culture conditions were optimized using a response surface methodology. CGTase excretion and cell lysis were analyzed by CGTase and β-galactosidase assays, respectively. High CGTase excretion with low cell lysis was achieved after the optimization process. The results suggest that optimization of the cell immobilization system increased CGTase excretion with low cell lysis and made it more valuable for industrial applications.